Record of Discussion Fifty Fourth Meeting National Development Council - Planning Commission (Planning Commission, 2007)
The National Development Council (NDC) held its 54th Meeting at Vigyan Bhavan, New Delhi on the 19th December, 2007 under the Chairmanship of Dr. Manmohan Singh, Prime Minister and Chairman of the Council to consider and approve the draft Eleventh Five Year Plan (2007-2012) Document.
Government of India Planning Commission
Government of India Planning Commission